Summary of the Prevention of Catheter-Associated Urinary Tract Infection in An Intensive Care Unit - Waluyo Waluyo; Yulia Indah Permata; Ulfa Nur Rohmah; Saskiyanti Ari Andini (Universitas Airlangga, 2019)
Background: Catheter-associated urinary tract infection is the most common type of nosocomial infection in an intensive care unit. The aim of this study was to examine the existing evidence of preventative measures against catheter-associated urinary tract infection being implemented to reduce urinary tract infection in intensive care units.Method: Databases were used to identify potential articles, namely Scopus, Pubmed, EBSCO and Proquest, limited to those published within the last 5 years from 2013 to 2018. The literature review used the keyword prevention, CAUTI and ICU. In the article search using “AND”, only 14 studies met the inclusion criteria. Across the 14 studies, 42486 participants and a mean 3540 per trial were included.Discussion: Nursing round, CAUTI bundle, bacitracin and cranberry, Nurse-driven protocol, protocol by team/ developmental protocol, surveillance of CAUTI, education, performance feedback, and general cultural practices alongside the American College of Critical Care Medicine and the Infectious Disease Society of America present guidelines that recommend CAUTI preventive practices that can be implemented to reduce the incidence of CAUTI in ICUs.Conclusion: From the several strategies used to prevent CAUTI, the most effective is the multidimensional approach because this approach combines several interventions and it also involves other practitioners. A multidimensional approach is more effective than a single dimensional approach in ICU.